STRATEGI RESILIENSI PEREMPUAN TERHADAP BODY SHAMING PADA KOMUNITAS RAMAH-RAMAH DI MEDIA SOSIAL X - Salma Reza Adinda; Dany Ardhian (Universitas Negeri Makassar, 2025)
This research aims to reveal women's resilience strategies in body shaming discourse conveyed on X social media in the Friendly-Friendly community feature, especially in terms of Sara Mills' Discourse Analysis Theory. This type of research is qualitative descriptive research. The data in this research is the text in tweets from Twitter users in the Friendly Community. The data collection technique is carried out using documentation techniques. The data analysis technique is carried out using the stages of data reduction, data presentation, and conclusions. The results of research on the subject-object position, women act as subjects and objects that are initially objectified, turn into active subjects. Meanwhile, the writer-reader position shows the writer's resilience and shows a discourse of resistance to body shaming. The forms of body shaming that women often experience focus on 3 forms, namely abbreviations, the use of metaphorical figures of speech, and the use of satirical figures of speech. Six aspects of resilience strategies were identified, namely optimism, emotional regulation, self-efficacy, problem analysis, impulse control, and reaching out.. The absence of empathy strategies shows that women focus on self-protection, self-acceptance, and seeking support from those around them.